Assessing the virulence of Cryptococcus neoformans causing meningitis in HIV infected and uninfected patients in Vietnam - Thanh, LT; Toffaletti, DL; Tenor, JL; Thwaites, GE; Ashton, PM; Baker, SG; Day, JN (Oxford University Press, 2020)
We previously observed a substantial burden of cryptococcal meningitis in Vietnam atypically arising in individuals who are uninfected with human immunodeficiency virus (HIV). This disease was associated with a single genotype of Cryptococcus neoformans (sequence type [ST]5), which was significantly less common in HIV-infected individuals. Aiming to compare the phenotypic characteristics of ST5 and non-ST5 C. neoformans, we selected 30 representative Vietnamese isolates and compared their in vitro pathogenic potential and in vivo virulence. ST5 and non-ST5 organisms exhibited comparable characteristics with respect to in vitro virulence markers including melanin production, replication at 37°C, and growth in cerebrospinal fluid. However, the ST5 isolates had significantly increased variability in cellular and capsular sizing compared with non-ST5 organisms (P < .001). Counterintuitively, mice infected with ST5 isolates had significantly longer survival with lower fungal burdens at day 7 than non-ST5 isolates. Notably, ST5 isolates induced significantly greater initial inflammatory responses than non-ST5 strains, measured by TNF-α concentrations (P < .001). Despite being generally less virulent in the mouse model, we hypothesize that the significant within strain variation seen in ST5 isolates in the tested phenotypes may represent an evolutionary advantage enabling adaptation to novel niches including apparently immunocompetent human hosts.